2021
DOI: 10.7759/cureus.14442
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Risk Factors Associated With Mortality in Critically Ill Patients With COVID-19

Abstract: To describe clinical characteristics and outcomes of ICU patients with COVID-19 and to investigate differences between survivors and non-survivors. MethodsDemographics, symptoms, laboratory values, comorbidities and outcomes were extracted retrospectively from the medical records of ICU patients with confirmed COVID-19 pneumonia from the Elisabeth-TweeSteden Hospital in Tilburg, the Netherlands from March until June 2020. Primary outcome was 28-day mortality and secondary outcomes were differences between surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(44 reference statements)
2
3
1
Order By: Relevance
“…This highlights the importance of preventative management and targeted vaccination strategies towards patients with COPD. We found an in-hospital mortality of 38.2%, which is consistent with similar studies in the early phase of the pandemic that have suggested mortality rates of 27.2%-61.5% [ 5 , 8 , 12 - 13 ]. The wide range of mortality may be due to the different endpoints used in studies that are typically either in-hospital or 30-day mortality.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This highlights the importance of preventative management and targeted vaccination strategies towards patients with COPD. We found an in-hospital mortality of 38.2%, which is consistent with similar studies in the early phase of the pandemic that have suggested mortality rates of 27.2%-61.5% [ 5 , 8 , 12 - 13 ]. The wide range of mortality may be due to the different endpoints used in studies that are typically either in-hospital or 30-day mortality.…”
Section: Discussionsupporting
confidence: 92%
“…In this retrospective study, we have attempted to explore the clinical characteristics and outcomes of ARDS patients in an urban population during the early phase of the COVID-19 pandemic. In terms of our demographics, our study had an average age of 64 for the total cohort, which is consistent with prior studies that have also reported an average age of intubated patients of around 64-68 years of age [5][6]8]. Also consistent with prior studies --hypertension, type 2 diabetes mellitus, and obesity were the most common co-morbidities [8].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the study of Leonardo et al, a significant correlation was found between mortality with RDW and APACHE-II score [24]. In their study, Vogels et al revealed that the SOFA score is an independent predictor of mortality in COVID-19 patients [25]. We also used the rapid Sequential Organ Failure Assessment (qSOFA) score, which is generally used to predict in-hospital mortality and intensive care unit admission in patients with sepsis, in our study [26].…”
Section: Discussionmentioning
confidence: 74%